The Application of Marine Natural Products (MNPS) In Anti-Covid-19 Therapeutics - Pawar, Rajendra Singh; Dimri, Mayank; Maithani, Alok; Kush, Luv (Asian Journal of Pharmaceutical Research and Development, 2020)
The bioprospecting of MNPs for the treatment of COVID-19 virus was attempted. The marine biodiversity is a remarkable source of bioactive chemotherapeuticals. The structural uniqueness of selected MNPs was correlatedwith reported binding energies to ascertain structure activity relationship (SAR) features.